2006
DOI: 10.1590/s0102-311x2006000600015
|View full text |Cite
|
Sign up to set email alerts
|

LER: trabalho, exclusão, dor, sofrimento e relação de gênero. Um estudo com trabalhadoras atendidas num serviço público de saúde

Abstract: Neste artigo, apresentamos os resultados da pesquisa qualitativa que desenvolvemos a partir do material de arquivo de um serviço de saúde referente a quatro grupos terapêuticos ocorridos entre 1995 e 1997. Nosso objetivo foi reconstruir a trajetória de vida e trabalho de portadoras das LER, considerando as suas relações com os familiares, parentes, amigos, empresa, colegas de trabalho, com os serviços de saúde e os impactos sobre a vida cotidiana. As informações descritas corroboram com os dados encontrados na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
4
0
6
Order By: Relevance
“…These differences are not yet clearly understood but some authors have suggested the role of physiological characteristics-women have more muscle fibers in the trapezoidal muscle than men [Lindman et al, 1991]; work-related factors-work posts are more adapted to men's needs [Ulin et al, 1993]; and work organization factors-women are regarded as objects, for example, machines [Hirata, 1998]. Higher MSD cases among women are explained by the fact that they hold more work posts facilitating the development of these injuries [Neves, 2006]. In the present study, three out of four women engaged in high-prevalence occupations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences are not yet clearly understood but some authors have suggested the role of physiological characteristics-women have more muscle fibers in the trapezoidal muscle than men [Lindman et al, 1991]; work-related factors-work posts are more adapted to men's needs [Ulin et al, 1993]; and work organization factors-women are regarded as objects, for example, machines [Hirata, 1998]. Higher MSD cases among women are explained by the fact that they hold more work posts facilitating the development of these injuries [Neves, 2006]. In the present study, three out of four women engaged in high-prevalence occupations.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological conditions such as depression may also be caused by tendinitis and tenosynovitis. Affected individuals can have distress, anguish, and despair, over the course disease because of pain at work, inadequate care provided in health services, injury chronification, therapy ineffectiveness, and inability to carry out daily activities such as use of public transportation, household chores, and personal care [Neves, 2006]. Moreover, there is evidence that people living in areas with higher education and health services, easier access to health care, and greater longevity are more able to perceive specific diseases [Sen, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Neves 19 enfatiza que a DORT pode ser decorrente da condição de trabalho e pode acometer ambos os sexos. Foi visualizado nesta revisão que a forma como é realizado o trabalho, o ambiente e a carga horária podem estar vinculados com comprometimentos, como a dor e desconforto verificados neste.…”
Section: Discussionunclassified
“…Segundo Neves (2006), as lesões por esforço repetitivo (LER), caracterizada também como Distúrbios osteomusculares relacionados ao trabalho (DORT), compreendem um conjunto de síndromes que afetam principalmente os membros superiores. A característica mais comum da doença é sua relação com o trabalho.…”
Section: Lesão Por Esforço Repetitivo (Ler)unclassified